Visual graphics for human rights, social justice, democracy and the public good - Vedant Nanackchand; Kim Berman (South African Journal of Education, 2012)
The value of human rights in a democratic South Africa is constantly threatened and often waived for nefarious reasons. We contend that the use of visual graphics among incoming university visual art students provides a mode of engagement that helps to inculcate awareness of human rights, social responsibility, and the public good in South African higher education. Visual graphics, the subject of the research project which forms a key component of a Masters dissertation by one of the authors, provides an opportunity to counter a noticeable decline in the students' response and sensitivity to the freedoms entrenched in the South African Bill of Rights. The article presents a study using an action research approach in the classroom between 2005-2010, in order to inculcate awareness of human rights among participating students and deepen their understanding of social responsibility. The method used involved an introduction to specific visual art curricular intervention projects which required incoming first-year students to develop visual responses to address selected human rights violations and, in their second year, to develop their visual voice in order to promote human rights advocacy through civic engagement. The critical outcomes impact positively on the use of graphic images in the curriculum as a visual methodology to re-insert the discourse of human rights as a basic tenet of constitutional democracy in higher education.